Incidence and risk factors of caesarean section in preterm breech births: A population-based cohort study. (May 2017) - Lorthe, Elsa; Quere, Mathilde; Sentilhes, Loïc; Delorme, Pierre; Kayem, Gilles
Abstract: Objectives: To describe the incidence of breech presentation at 22–34 weeks' gestation, estimate the incidence of cesarean section delivery by cause of prematurity, and assess the factors associated with caesarean delivery in preterm breech births with preterm labor or preterm premature rupture of membranes. Study design: EPIPAGE 2 is a French national prospective population-based cohort study of preterm births that occurred in 546 maternity units in 2011. We estimated the overall incidence of breech presentation and the incidence of cesarean delivery by cause of prematurity. Among the 579 singletons with breech presentation born at 22–34 weeks in a context of spontaneous preterm labor or membrane rupture, multivariable logistic regression was used to assess the association between individual and institutional characteristics and caesarean delivery. Results: Among the 3660 singletons born at 22–34 weeks' gestation in the EPIPAGE 2 study, 20.1% (n = 911) were breech presentation. Among these births, the rate of cesarean section was 99.6% with vascular pathologies, intrauterine growth retardation or placental abruption as compared with 60.1% with spontaneous preterm labor or membrane rupture. The main indication for caesarean delivery was gestational age associated with breech presentation (61.0%). Delivery mode varied by region of birth. Other characteristics associated with caesarean delivery were hospital status (public teaching, public non-teaching or private), clinical chorioamniotitis, hospital admission after labor onset, and gestational age. Conclusion: Breech presentation is common in preterm infants and is associated with widespread use of cesarean delivery with significant regional disparities that could reflect the lack of consensus and recommendations on the preferential mode of delivery. Other factors associated with caesarean delivery are the status of the maternity unit, clinical chorioamniotitis, admission after labor onset and gestational age.